Effect of biol and deficit irrigation applications on the agronomic performance of lettuce crop - Simbaña-Cifuentes, Belén Estefanía (2025)
Introduction. Biol and deficit irrigation reduce the use of synthetic fertilizers and optimize water use, respectively. Objective. To analyze the impact of a leaf litter-based biol and deficit irrigation on lettuce cultivation (Lactuca sativa L.). Materials and methods. A randomized complete block design with a 2 × 3 factorial arrangement was used. The evaluated treatments were T1 (without biol + 100 % of ETc), T2 (without biol + 75 % of ETc), T3 (without biol + 50 % of ETc), T4 (with biol + 100 % of ETc), T5 (with biol + 75 % of ETc), and T6 (with biol + 50 % of ETc). The evaluated variables included physicochemical characterization of the biol, agronomic performance of the crop (root diameter, root length, leaf length, number of leaves, total weight, commercial weight, yield, and dry matter), and water use efficiency. Results. The biol showed a pH of 5.6, electrical conductivity of 6.92 dS/m, and a temperature of 22.5 °C, as well as high levels of essential nutrients such as nitrogen, potassium, calcium, and iron. Regarding heavy metals such as cadmium and lead, concentrations remained within internationally acceptable standards. Agronomically, significant differences were observed in plant height, root diameter, leaf length, number of leaves, and total weight between treatment T4 (with biol + 100 % of ETc) and T3 (without biol + 50 % of ETc). However, no statistical differences were found in the remaining variables. Conclusions. Biol improved the cultivation of Lactuca sativa L. T4 showed the highest yield, while T6 reached 21.04 kg/m³, suggesting more efficient water use under deficit irrigation.